Effect of soccer practice on the executive functions of children and adolescents. A systematic review study (Research, Society and Development, 2021)
Introduction: Sports practice begins between childhood and adolescence with the goal of motor learning. Football practice has beneficial effects on physical and motor skills. Recent studies have demonstrated the potential of childhood soccer practice to stimulate cognitive development. Objective: To verify, through a systematic review, the effects of soccer practice for children and adolescents in the cognitive and motor domains. Methods: SciELO and PubMed databases were searched using the terms (soccer OR soccer) associated with (executive functions OR executive functions), (cognitive functions OR cognitive functions) associated with (soccer OR soccer) from 2010 to 2020, 402 articles were found. After exclusion criteria, nine articles remained. Results: The most evaluated components were the executive functions, which appear in the 9 studies and the selective attention that was investigated in 6 studies. The selected articles obtained a sample of 1069 participants. Eight works associated executive functions to the practice of football. In six studies, it was observed that athletes from 7 to 17 years old who trained football professionally obtained better results in cognitive tests compared to those who trained in amateur clubs or did not train the sport. Conclusion: The results indicate a positive relationship in the improvement of the capacity of executive functions among children and adolescents who started soccer in the latency period.